State of knowledge and conservation of the snake fauna of the “Brejos de Altitude” in the Pernambuco Endemism Center, Northeastern Brazil - Pereira Filho, Gentil Alves; Freitas, Marco Antonio; Vieira, Washington Luiz Silva; Moura, Geraldo Jorge; França, Frederico Gustavo (Ethnobiology and Conservation, 2020)
The Atlantic Forest is originally distributed along the Brazilian coast from the states of Rio Grande do Norte to Rio Grande do Sul, and it presents many different vegetal physiognomies. Brejos de Altitude is a set of relict altitudinal forests in northeastern Brazil with a distinct and poorly studied biota representing special areas within the Atlantic Forest. The snake fauna of these forests is still poorly understood despite the increasing amount of information available. The aim of this study was to furnish the current state of knowledge and conservation of the snake fauna at the Brejos in the Pernambuco Endemism Center. The database used here is based on the materials housed at Museu de Zoologia da Universidade de São Paulo and the herpetological collections of Universidade Federal da Paraíba and Universidade Federal Rural de Pernambuco, in addition to literature records. Out of 7 families, 37 genera and 63 species were found in Brejos de Altitude, and no species appeared in the list of endangered fauna of Brazil. The results showed species with strong dependence on forest and species distributed in open areas, such as Caatinga and Cerrado, although, many Brejos showed no data on snake fauna. In conclusion, Brejos de Altitude is a threatened region of the Atlantic Forest with a small number of protected areas and high rates of deforestation, thus needing urgent conservation actions.